Predictive value of MMP-2, MMP-9, TIMP-1 in surgical treatment of localized renal cell cancer - A. I. Tarasenko (Issledovaniâ i Praktika v Medicine, 2021)
Purpose of the study. To determine the association of individual biomolecular markers of oncogenesis MMP‑2, MMP‑9 and the inhibitor of metalloproteinases TIMP‑1 with the risk of tumor invasion and metastasis in the early and late postoperative period in various types of surgical treatment of RCC.Materials and methods. The study prospectively included medical data of 60 patients with kidney cancer with T1-3N0 M0 who received surgical treatment at the Urology Clinic of the S.R.Mirotvortsev Design Bureau of the SSMU from 2016 to 2019. The patients were divided into 3 groups: 1st group included 20 patients who underwent kidney resection for elective indications, with tumors of the renal parenchyma; 2nd group – 20 patients who underwent radical nephrectomy by laparoscopic approach; Group 3-20 patients who underwent radical nephrectomy with lumbotomy access. All patients being in the early (7-10th day) and long-term postoperative period (after 1 and 2 years) by solid-phase ELISA, on a StatFax 4200 analyzer using eBiosence and Cloud-Clone Corp reagent kits, a study was made on the basis of the concentration in the blood serum of markers of oncogenesis MMP‑2, MMP‑9 and TIMP‑1 metalloproteinase inhibitor.Results. In all groups of patients with RCC, an initial increase in the concentration of MMP‑9 was revealed compared to the control (p≤0.05). According to the results of the ROC analysis, this indicator has a high specificity and sensitivity in terms of predicting RCC at the preoperative stage. The highest sensitivity and specificity for detecting tumor progression was demonstrated by matrix metalloproteinases: MMP‑2 – sensitivity 96 %, specificity 67 % (cut-off point 357.5 pg/ml) and MMP‑9 – sensitivity 87.5 % and specificity 62 % (cut-off point 958 ng/ml). At the same time, TIMP‑1 showed less significant indicators – sensitivity and specificity (74 % and 60 %, respectively) with a cut-off point of 0.49 ng/ml.Conclusion. Serum MMP‑2 and MMP‑9 are a marker of a poor prognosis for the progression of RCC. Elevated levels of MMP‑9 in the blood serum of RCC patients before and after various types of surgical treatment reflect the individual characteristics of the patient’s body and the tumor process. Dynamic monitoring of the level of markers of oncogenesis in patients with RCC allows a personalized approach to the choice of the scope and method of surgical treatment of RCC.